ANALISIS PENJUALAN BARANG LARIS DAN KURANG LARIS TERHADAP PERCETAKAN AWFA DIGITL PRINTING MENGGUNAKAN METODE DECISION TREE DENGAN OPTIMASI ALGORITMA GENETIKA - Suherman Suherman; Irham Muzaky2 (Teknik Informatika, Universitas Pelita Bangsa, 2019)
Data mining is the process by which data can be searched for with interesting patterns or information with selected data used by certain methods. Problems found in selling items that are in demand and not selling are needed A method for classifying what is the best-selling and least- selling item is needed. C4.5 algorithm is an algorithm used to build a decision tree (decision preparation). C.45 algorithm is one of the decision tree induction algorithms. The goal is to optimize the C4.5 Decision Tree Algorithm with Genetic Algorithms. The use of the C4.5 Decision Tree Algorithm method yields 85.15%, while the results after being optimized using the Genetic Algorithm reach 93.09%. Thus the results of optimization of the C4.5 Algorithm Decision Tree + Genetic Algorithm can increase the accuracy value resulting in more optimal accuracy. It can be denied from the result of the predicted sales of goods reaching 37 after being optimized to 121, when the prediction results are less than 133 after being optimized to 524. Keywords : C4.5 Decision Tree Algorithm, Genetic Algorithm, Optimization, Analysis.